Assessment of the NDVI and TCC Greenness in the detection of vegetation based on Landsat satellites in the Upper Mutha basin, Pune District (International Journal of Food and Nutritional Sciences, 2022)
Vegetation is essential to the survival of life on Earth. It absorbs carbondioxide and produces oxygen for human breathing, which helps to regulate theclimate. Plants support a wide range of organisms by acting as food and shelter,increasing biodiversity.